What Position Should Indonesia Have in Placing Its Renewable Energy Development and Energy Transition Plan? - Nugroho, Hanan; Dedi Rustandi; Nur Laila Widyastuti (Bappenas Working Papers, 2021)
Indonesia’s energy face a situation of giddiness in deciding a transition that requires a much larger use of renewable energy, as the country is basically a fossil fuels one but in the other side it is demanded to contribute a bigger role in efforts to mitigate global climate change. Development of Indonesia's energy-environment policies, particularly on renewable energy is highlighted. International agreements on global climate change and Indonesia's participation are described. Foundations of the successful renewable energy development are emphasized. It recommends publishing a renewable energy law, establish regulation regarding renewable energy pricing, develop a carbon pricing system, establish organizational unit regarding energy-climate change, develop renewable energy technology, improve data quality dan grid intrconnection, implement energy conservation, encourage development of REBID and REBED.